Comparing digestibility of A- and B- type crystals and providing Insight on digestibility of starches - Cai, Liming (Kansas State University, 2011)
Starch is the most important source of food energy. However, the information about the metabolic quality of starchy foods is scarce. It is well known that native starches with a B-type X-ray diffraction pattern are more resistant to alpha-amylase digestion than those starches with an A-type X-ray pattern, but the underlying mechanism is not well understood. It is not clear whether the enzyme resistance of B-type starch is due to its B-type crystalline structure or the other structural features in starch granules. The objective of this study was to compare the structure and enzyme digestibility of highly pure A- and B-type starch crystals, and understand the roles of crystalline types in starch digestibility. Highly pure A- and B-type starch crystals were prepared from short linear α-glucans (short-chain amylose) generated from completely debranched waxy starches by manipulating the processing conditions such as starch solids concentration, crystallization temperature and chain length. High concentration, high temperature and short chain length favored the formation of the A-type structure, whereas reverse conditions resulted in the B-type polymorph. Digestion results using a mixture of α-amylase and glucoamylase showed that A-type crystals were more resistant to enzyme digestion than B-type crystals. The A-type crystalline product obtained upon debranching 25% waxy maize starch at 50ºC for 24 h gave 16.6% digestion after 3 h, whereas B-type crystals produced by debranching 5% waxy maize starch at 50ºC for 24 h followed by holding at 25ºC for another 24 h had 38.9% digested after 3 h. The A-type crystals had a higher melting temperature than the B-type crystals as determined by differential scanning calorimetry. Annealing increased the peak melting temperature of the B-type crystals, making it similar to that of the A-type crystals, but did not improve the enzyme resistance. The possible reason for these results was due to more condense packing pattern of double helices in A-type crystallites. It seems that the crystalline types are not the key factor that controls the digestibility of native starch granules. The resistance of native starches with B-type X-ray diffraction pattern is probably attributed to the other structural features in starch granules.
Keywords: Waxy starch; Short-chain amylose; Crystalline type; Debranching; Spherulites; Digestibility; Agriculture, General (0473); Food Science (0359)